Positive psychology for teachers - Swinson, Jeremy; Harrop, Alex. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2012)
"Practical, actionable information about the positive, behavioural approach to education is in desperately short supply, and yet when implemented properly the impact on school behaviour and achievement can be enormous. Positive Psychology for Teachers aims to address this gap. Written by experienced practitioners, it gives teachers simple and direct advice on how they can use the positive behavioural approach for the benefit of their pupils and schools. Based on the authors' own experiences of intervention in school settings, this practical guide includes a number of vignettes and case studies illustrating how the behavioural approach has been used by teachers in a wide variety of classrooms to make their teaching more effective. Each case study will be followed by a number of suggested practical activities for classroom implementation. Throughout the book background theory is explained in a concise and easily digestible manner and activities are clearly explained with benefits and end goals clearly signposted. Areas covered include:- - Whole school interventions, turning around under-performance - Reducing disruptive behaviour in the classroom - Improving creative writing and increasing reading attainment - Improving pupils' self concepts - SEN interventions including autism, children with challenging behaviour and those classified as having social, emotional and behavioural difficulties - The difference between teachers' treatment of boys and girls - Strategies for turning around the behaviour of very difficult pupils This practical user-friendly text is aimed directly at trainee and practicing teachers but would also be very relevant to those working with trainee teachers in university departments and to educational psychologists"--
Includes bibliographical references (pages [149]-158) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Educational psychology; Classroom management; Behavior modification; Electronic books